EKSPLOITASI ISU POLITIK IDENTITAS TERHADAP IDENTITAS POLITIK PADA GENERASI MILINEAL INDONESIA DI ERA 4.0 - Soenjoto, Wening Purbatin Palupi (UIN Walisongo Semarang, 2019)
Indonesia has a collective culture that illustrates the recognition of togetherness, mutual cooperation and cohesiveness. But it is also prone to conflicts if there are differences, especially in the generation of millennials who are easily herded through the power of social media or sophisticated communication media in the era of 4.0. Millennial generation at the age of age who is still young to digest and understand in a mature and healthy manner. Identity is politicized through various and extreme interpretations, which aims to get support from the millennial generation who feel 'the same', both in race, ethnicity, religion, and other adhesive elements so that movements or polarization of oppositional dichotomy features become easy to become the main foundation that differentiate feelings of collectivity so that exploitation is easy, then intolerance is increasing. The occurrence of social imagery mismatches about political identity and political identity that occurs in the current millennial generation. This study aims to determine the effect of the issue of identity politics towards political identity in Indonesian millennial generation in the 4.0 era and trying to answer the formulation of the problem, namely: first, describing the exploitation of identity political issues that began to develop in Indonesian society in the 4.0 era. Second: describing the process of political exploitation of identity political identity in the millennial generation. Third: finding implications of the meaning of the results of research and solutions that can add to the study of the exploitation of the issue of identity politics on political identity in Indonesian millennial generation in Era 4.0 so that it can be further investigated by subsequent researchers. The method used in this study is a qualitative method with descriptive analysis. The research subjects were 150 students, aged 19-21 years who provided research data through interviews, surveys and documentation with triangulation data processing in order to obtain valid research results. Based on the results of the study, the conclusion was drawn. the exploitation of the issue of identity politics against political identity in Indonesia's millennial generation in era 4.0.